Reconstrução de imagens de ultrassom utilizando regularização l1 através de mínimos quadrados iterativamente reponderados e gradiente conjugado - Passarin, Thiago Alberto Rigo (2013)
This work presents an inverse problem based method for ultrasound image reconstruction which uses the L2-norm (or euclidean norm) as a penalty for the error between the data and the solution, and the L1-norm as a regularization penalty. The motivation for the use of of L1 regularization is the sparsity promoting property of this type of regularization. The sparsity of L1 regularization circumvents the problem of excess of artifatcts that is observed in other approaches of inverse problem based reconstrucion in ultrasound. Such problem is mainly a consequence of the limitation in the discrete representation of a continuous object in the acquisition model. Due to this limitation, reflecting objects in the imaged area are often localized in positions that do not correspond precisely to one of the positions in the discrete model, therefore generating data that do not correspond to the model data. The formulations of the problem with L2 regularization and with L1 regularization are presented and compared in geometric and Bayesian terms. The optimization algorithm proposed is an implementation of Iteratively Reweighted Least Squares (IRLS) and uses the Conjugate Gradient (CG) method inside each iteration, thus being called IRLS-CG. Simulations with computer phantoms are realized showing that the proposed method allows for the reconstruction of images, without observable artifacts, from data with reflectors located in non-modeled positions. Simulations also show a better spatial resolution in the proposed method when compared to the delay-and-sum (DAS) algorithm. It was also observed better computational performance of CG when compared to the matrix inversion in the iterations of IRLS.